(untitled) (Journal of Dhaka Medical College, 2015)
Castleman disease (CD) or angiofollicular lymph node hyperplasia is an uncommon benign lymphoproliferative disorder. Sometimes it is related to the chronic human herpes virus 8 (HHV-8) infection and the human immunodeficiency virus (HIV). Two clinical entities have been described: a unicentric presentation with the disease confined to a single anatomic lymph node and a multicentric presentation characterized by generalized lymphadenopathy and a more aggressive clinical course. Also, three histopathological subtypes have been described: hyalinevascular, plasma cell, and a mixed variant.We report the case of a 22-year-old young man who was diagnosed as unicentric Castleman Disease. We found on routine physical examination a mass localized in the left abdomen without clinically important constitutional symptoms for 3 years. Abdominal ultrasound and computed tomography scans revealed minimally enhancing soft tissue density lesion & it was seen in the left para aortic region measuring about 71mm x 42 mm in size. The patient subse-quently underwent an exploratory laparotomy. After opening of the abdomen, a lump measuring about 8 cm x 5 cm was found in the mesentery. The whole lump was dissected out and the gap in the mesentery was closed. No other lymphadenopathy was found. The specimen was sent for histopathology which revealed Castleman disease, plasma cell type. The patient completely recovered after surgery. Castleman disease is commonly misdiagnosed as malignant lymphoma, lymphadenitis or ectopic thymoma. So far, its diagnosis is mainly achieved via histopathological examination of surgically obtained tissue. Local or unicentric CD has a good prognosis if surgically excised properly. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 256-258